Humeral stem lucencies correlate with clinical outcomes in anatomic total shoulder arthroplasty - LaChaud, Gregory Y. (JSES Int, 2020)
BACKGROUND: Humeral stem lucencies are uncommon after uncemented anatomic total shoulder arthroplasty (aTSA), and their clinical significance is unknown. This study compares clinical outcomes of aTSA with and without humeral stem lucencies. METHODS: Two-hundred eighty aTSAs using an uncemented grit-blasted metaphyseal-fit humeral stem between 2005 and 2013 were retrospectively evaluated for radiographic humeral stem lucencies. All shoulders were evaluated at a minimum 5-year follow-up from a multicenter database. Clinical outcomes included range of motion (ROM) and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) score, Constant score, University of California–Los Angeles Shoulder Score (UCLA), Simple Shoulder Test (SST), and Shoulder Pain and Disability Index (SPADI) scores. Postoperative radiographs were evaluated and complications were recorded. RESULTS: Two-hundred forty-three humeral stems showed no radiolucent lines. Among the 37 humeral stems with lucent lines, lines were most common in zones 8, 4, 7, and 3. Preoperative ROM and functional outcomes were similar between groups. Postoperative change in outcomes exceeded the minimal clinically important difference (MCID) for all ROM and outcomes in both groups. Postoperative change between groups showed no significant difference in ROM or outcome scores, but improved mean abduction exceeded the MCID in the patients without humeral lines. The complication rate after omitting patients with humeral loosening was higher in patients with humeral lucencies, as was the revision rate. There was also a higher glenoid-loosening rate in patients with humeral lucencies. CONCLUSION: Humeral lucent lines after uncemented stemmed aTSA have a small negative effect on ROM and functional outcomes compared with patients without lucent humeral lines, which may not be clinically significant. The complication and revision rates were significantly higher in patients with humeral lucencies.